Counsel's Procedural Objection Under Indonesia's 2025 Criminal Procedure Code: Safeguarding Suspects and Regulating Unlawfully Obtained Evidence - Purnomo Nur Sidi; Annisa Nur Fitriyani (Punggawa Legacy Center, 2026)
Indonesia's 2025 Criminal Procedure Code expressly authorizes defence counsel to object when investigators intimidate a suspect or use trapping questions, yet it does not state what follows when the objection is obstructed, ignored, or incompletely recorded. This article examines the legal character, scope, and consequences of that new authority through normative legal research using statutory and conceptual approaches. It argues that Article 32 transforms legal assistance during suspect examination from physical attendance into participatory defence. The objection operates as an immediate corrective intervention and a documentary safeguard, while the investigator bears a correlative duty to record it regardless of agreement with counsel's assessment. Intimidation should be assessed by its effect on the suspect's freedom to provide or refuse information, whereas a trapping question embeds an unaccepted premise and narrows the suspect's answer around it. An ignored objection does not automatically nullify the examination record or the entire investigation. Its evidentiary consequence depends on a demonstrable connection between the procedural violation and evidence later tendered at trial. Under Article 235, only a judicial finding that evidence was unlawfully obtained triggers non-use and the loss of probative force. The article proposes a graduated legal-consequence model that separates obstruction of counsel, defective recording, continued improper questioning, evidentiary exclusion, and personal accountability of investigators.